2012
DOI: 10.1007/s11192-011-0599-z
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric study of earthquake research: 1900–2010

Abstract: We evaluated earthquake research performance based on a bibliometric analysis of 84,051 documents published in journals and other outlets contained in the Scientific Citation Index (SCI) and Social Science Citation Index (SSCI) bibliographic databases for the period of 1900-2010. We summarized significant publication indicators in earthquake research, evaluated national and institutional research performance, and presented earthquake research development from a supplementary perspective. Research output descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(63 citation statements)
references
References 26 publications
4
58
0
1
Order By: Relevance
“…Firstly, the amount of research on GLOFs had an exponentially increasing trend in the WOS database between 1979 and 2016. From the field of natural hazard science, a similar trend is observed in research on tsunamis (Chiu and Ho, 2007), a more remarkable trend is observed in research on landslides (Xu et al, 2015) and a less remarkable trend is observed in research on earthquakes (Liu et al, 2012). This trend is similar de- Table 4.…”
Section: Analysis Of the Contentsupporting
confidence: 71%
See 2 more Smart Citations
“…Firstly, the amount of research on GLOFs had an exponentially increasing trend in the WOS database between 1979 and 2016. From the field of natural hazard science, a similar trend is observed in research on tsunamis (Chiu and Ho, 2007), a more remarkable trend is observed in research on landslides (Xu et al, 2015) and a less remarkable trend is observed in research on earthquakes (Liu et al, 2012). This trend is similar de- Table 4.…”
Section: Analysis Of the Contentsupporting
confidence: 71%
“…and Ho, 2007;Liu et al, 2012;Wu et al, 2015). While the amount of research on GLOFs has gradually increased over the past few decades (see Emmer et al, 2016), detailed insight into the GLOF research community, its global bibliometrics and geographies of research is missing.…”
Section: A Emmer: Glofs In the Wosmentioning
confidence: 99%
See 1 more Smart Citation
“…The emerging bibliometric network analysis often analyzes the relationships among keywords, country, research institute, and author. The common network analysis includes co-word analysis [33][34][35], co-citation analysis [36,37], co-authorship analysis [38][39][40], and co-publication analysis [41]. Many disciplines have used bibliometric methods to explore the impact of research themes, such as natural science, engineering, business, social sciences, and humanities [42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies exist that focus on a scientometric / bibliometric analysis of various research fields and their geographies (e.g., Small and Garfield, 1985), including those in geomorphology (e.g., Dorn, 2002), river research (e.g., Vugteveen et al, 2014), and natural hazard science (e.g., Chiu and Ho, 2007;Liu et al, 2012;Wu et al, 2015). While the amount of research of GLOFs has gradually increased over the past few decades (see Emmer et al, 2016), detailed insight into 10 the GLOF research community, its global bibliometrics and geographies of research is missing.…”
mentioning
confidence: 99%